Intelligent pressure-controlled percutaneous unroofing: advancing minimally invasive renal cyst treatment - Liao, Haijun; Zhai, Qiliang; Huang, Xin; Du, Chuance; Fan, Difu; Li, Yadong; Song, Leming (Frontiers in Medicine, 2025)
ObjectiveSimple renal cysts (SRC) are common benign lesions that may require surgical intervention when symptomatic. This study aimed to compare the efficacy and safety of intelligent pressure-controlled percutaneous unroofing of renal cysts (IPC-PURC) with laparoscopic unroofing of renal cysts (LURC) in the treatment of SRC.Patients and methodsA retrospective analysis was conducted on 168 patients with SRC who underwent either IPC-PURC (n = 61) or LURC (n = 107) between December 2017 and December 2023. Key outcomes, including operative time, postoperative hospital stay, drainage duration, postoperative pain scores, hemoglobin decrease, and complication rates, were compared between the two groups.ResultsThe IPC-PURC group demonstrated significantly shorter operative times (78.3 ± 22.8 min vs. 108.6 ± 29.6 min, p < 0.001), postoperative hospital stays (4 days vs. 5 days, p < 0.001), and drainage tube durations (3 days vs. 4 days, p < 0.001) compared to the LURC group. Additionally, patients in the IPC-PURC group reported lower postoperative pain scores (p < 0.001). No significant differences were observed between the two groups in terms of hemoglobin decrease or complication rates. Both techniques achieved a 100% success rate in symptomatic relief and cyst resolution.ConclusionIPC-PURC offers advantages in terms of shorter operative time, reduced postoperative hospital stay, and lower postoperative pain compared to LURC, while maintaining similar safety profiles and efficacy. Therefore, IPC-PURC may represent a superior minimally invasive option for the treatment of SRC.